2005
DOI: 10.1215/s1152851704000997
|View full text |Cite
|
Sign up to set email alerts
|

Flavopiridol downregulates hypoxia-mediated hypoxia-inducible factor-1α expression in human glioma cells by a proteasome-independent pathway: Implications for in vivo therapy

Abstract: Angiogenesis is a critical step required for sustained tumor growth and tumor progression. The stimulation of endothelial cells by cytokines secreted by tumor cells such as vascular endothelial growth factor (VEGF) induces their proliferation and migration. This is a prominent feature of high-grade gliomas. The secretion of VEGF is greatly upregulated under conditions of hypoxia because of the transcription factor hypoxiainducible factor (HIF)-1alpha, which controls the expression of many genes, allowing rapid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 39 publications
(51 reference statements)
2
50
1
Order By: Relevance
“…Previous studies revealed that the Cdk inhibitor flavopiridol decreased HIF-1α levels and HIF target gene expression (55,56). This effect was noted to be proteasome-independent, although the molecular mechanism was not delineated (55).…”
Section: (D and E) Mouse Mefs Frommentioning
confidence: 97%
“…Previous studies revealed that the Cdk inhibitor flavopiridol decreased HIF-1α levels and HIF target gene expression (55,56). This effect was noted to be proteasome-independent, although the molecular mechanism was not delineated (55).…”
Section: (D and E) Mouse Mefs Frommentioning
confidence: 97%
“…[43][44][45] Thus, agents that can block radiation-induced VEGF secretion or its binding to its receptor, VEGFR, are two strategies that have been used to increase anti-tumor effects of radiation. [21][22][23][44][45][46][47][48] Although the mechanisms by which flavopiridol enhanced anti-tumor effects when combined with radiation were not evaluated in this study, based on its known anti-angiogenic activity in a variety of in vivo models, 14,16,49,50 it is likely that one mechanism involved is due to its ability to inhibit angiogenesis. Recently, we demonstrated that flavopiridol inhibited the HIF-1 pathway by downregulation of HIF-1α expression, concomitant with decreased VEGF secretion by glioma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we demonstrated that flavopiridol inhibited the HIF-1 pathway by downregulation of HIF-1α expression, concomitant with decreased VEGF secretion by glioma cells. 16 When we analyzed vascular density in intracranial GL261 tumors from control and flavopiridol treated animals, the tumors from drug-treated animals had significantly fewer blood vessels compared with tumors from control animals, suggesting that flavopiridol inhibited angiogenic activity. 16 This conclusion is further supported by two other recent in vivo studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations